Family, friends, and financial know-how: influences on students' intentions to pursue entrepreneurship, with the moderating role of self-efficacy - Indradewa, Rhian; Setiawan, Rizki Muharom (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aims to examine the influence of family economic education, peer groups, economic literacy, and self-efficacy on students' entrepreneurial intentions. The research utilizing a survey method with a Likert scale distributed to 292 students actively enrolled in universities in the Greater Jakarta area Indonesia. Data analysis was conducted using PLS-SEM. The results indicate that family economic education and peer groups have a positive and significant effect on economic literacy and entrepreneurial intentions. Economic literacy was found to mediate the influence of family economic education and peer groups on entrepreneurial intentions. Furthermore, self-efficacy moderates the relationship between economic literacy and entrepreneurial intentions, enhancing the impact of economic literacy on entrepreneurial intentions when self-efficacy is high. This research offers valuable insights and implication managerial for developing entrepreneurship education programs that involve families and create positive peer interactions among students. It suggests the need for educational institutions to integrate family-based economic education workshops and seminars, as well as establish entrepreneurship clubs and networking events to foster a conducive environment for entrepreneurial growth. Strengthening self-efficacy through personal development programs is also recommended to ensure that students can effectively apply their economic literacy in entrepreneurial contexts. These combined efforts can significantly enhance entrepreneurial intentions among students, contributing to reducing unemployment rates and promoting economic growth in Indonesia.